Bayesian evolution analyses suggests the global spread of Xanthomonas cynarae pv. gardneri occurred during the global adoption of hybrid tomato seed - (:unkn) unknown (My University, 2019)
Xanthomonas cynarae pv. gardneri (formerly, X. gardneri, Xg) is one of the four species causing bacterial spot of tomato and pepper. For more than four decades, only the reference strain isolated from Yugoslavia in 1957 was known. While two strains were isolated from Costa Rica in the early 1990s, recently, especially in the late 1990s to the 2000s, strains were recovered from several countries around the world where they cause significant yield loss. In this study, we sequenced genomes of strains from Brazil, Canada, Costa Rica, Ethiopia, Reunion, Uruguay, USA and South Africa to study global diversification and spread. Pangenome analysis was carried out using Roary while recombination was inferred using ClonalFrameML. Aligned core genes were used for inferring maximum likelihood phylogeny. For calling Single nucleotide polymorphisms, the Snippy pipeline was used. After correcting the dataset for molecular clock signal using TempEst, we used the program BEAST to infer time-calibrated Bayesian analyses under various evolutionary models. Our results show a near clonal population for Xg, with few strains having unique recombination hotspots. Time- calibrated Bayesian analyses suggests the reference strain and the current global population diverged more than two hundred years ago. The major diversification of the current global population took place in 1975–1985, which coincides with the period of expansion in the global use of hybrid tomato seeds. Our results are important in understanding the evolution and global spread of plant pathogens as trade in seeds become globalized.
Keywords: African Research